Climate shocks and fertilizer responses: Field-level evidence for rice production in Bangladesh - Takeshima, Hiroyuki; Kishore, Avinash; Kumar, Anjani (International Association of Agricultural Economists, 2024)
The fertilizer response of yield has been one of the major indicators of agricultural productivity in both developed and developing countries. Filling the evidence gap remains vital regarding fertilizer response in Asia, particularly in South Asia, given the evolution and emergence of new challenges, including intensifying climate shocks. We aim to partly fill this knowledge gap by investigating the associations between climate shocks and fertilizer response in Bangladeshi rice production. Using three rounds of nationally representative farm household panel data with plot- level information, we assess fertilizer response functions regarding rice yield and how the shapes of these response functions are heterogeneous in relation to anomalies in temperatures, droughts, and rainfall. We find robust evidence that climate anomalies have adverse effects on fertilizer responses, including higher temperatures for the Boro and the Aman irrigated systems and higher temperatures and droughts for the Aman rainfed systems. These findings hold robustly under various fertilizer response function forms, i.e., polynomial function and stochastic Linear Response Plateau. Furthermore, results for stochastic Linear Response Plateau are also consistent for both switching regression type models and Bayesian regression models.